Cryptosystem using Chaotic Shuffling Hill pad Encryption Scheme for Secure Data Transmission - Vimalraj, T. Jaison; Mithun, P; Mathiyarasu, K (International Journal of Computer Sciences and Engineering, 2025)
Maintaining privacy and security of any data, specifically for images that are transmitted through network is a major issue in today’s world. In this paper, a new three level Chaotic Shuffling Hill Pad encryption (CSHP) scheme is proposed. In first level encryption, the input image is subdivided and shuffled using chaotic algorithm. In second level, the shuffled blocks are encrypted using subset Hill algorithm with different product keys. Third level encryption is performed with the basis of Onetime pad encryption algorithm, in order to tighten the security of the image. Finally, the encrypted image is converted to text file, which is the intended cipher format. Product keys are chosen in such a way that they are invertible. The encrypted text file transmitted through insecure channel can be decrypted at the receiver’s end. The proposed method is tested with various standard images and the results are encouraging. The proposed method finds its application in Defence field